Chemical Constituents from Calophyllum Inophyllum and Cratoxylum Arborescens and Their Biological Activities - Jong, Vivien Yi Mian (2007)
Chemical and biological studies were carried out on two plants, Calophyllum inophyllum (Guttiferae) and Cratoxylum arborescens (Guttiferae). The chemical investigation covered triterpenoids, quinones and xanthones. These compounds were isolated using common chromatographic techniques and were identified using spectroscopic experiments such as NMR, MS, IR and UV. Calophyllum inophyllum (root bark) afforded sitosterol (71) and six other known xanthones which are brasilixanthone (72), inophyllin A (26), inophyllin B (27), 1,3,5-trihydroxy-2-methoxy xanthone (73), caloxanthone A (74) and pyranojacareubin (75). Meanwhile, studies on Cratoxylum arborescens (stem bark) provided one triterpenoid, friedelin (76) together with three others known quinones. These are vismione (77), vismiaquinone (78), and 1,8-dihydroxy-3-methoxy-6-methyl anthraquinone (79).Cytotoxic tests were carried out using CEM-SS cell line and HL-60 cell line. The crude hexane extract of Cratoxylum arborescens B. was found to be inactive to cytotoxic activity. The crude chloroform and methanol extracts of Cratoxylum arborescens B. showed good cytotoxic activity with IC50 values of 16 and 18 μg/ml, respectively. Meanwhile, the crude chloroform extract of the stem bark of Calophyllum inophyllum L. also showed a good cytotoxic activity with an IC50 value of 17 μg/ml. Two pure compounds obtained from Calophyllum inophyllum L., inophylin B (26) and caloxanthone A (74) also showed good activities against the HL-60 cell line with IC50 values of 15 and 29 μg/ml respectively. The antimicrobial activity test was also carried out using four pathogenic bacteria, namely, Methicilin Resistant Staphylococcus aures, Pseudomonas aeruginosa, Staphylococcus typhimurium and Bacillus subtilis. However, most of the crude extracts gave only moderate or weak activity. The larvicidal tests were performed against the larvae of Aedes aegypti using the WHO (1981) standard procedures with slight modifications. The crude hexane, chloroform and methanol extracts of Calophyllum inophyllum and Cratoxylum arborescens were inactive against the larvae of Aedes aegypti. No activity was recorded for the antifungal activity test